2012
DOI: 10.1038/nmat3289
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity-based single-shot subwavelength coherent diffractive imaging

Abstract: Coherent Diffractive Imaging (CDI) is an algorithmic imaging technique where intricate features are reconstructed from measurements of the freely diffracting intensity pattern. An important goal of such lensless imaging methods is to study the structure of molecules that cannot be crystallized. Ideally, one would want to perform CDI at the highest achievable spatial resolution and in a single-shot measurement such that it could be applied to imaging of ultrafast events. However, the resolution of current CDI t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
150
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(152 citation statements)
references
References 32 publications
1
150
0
1
Order By: Relevance
“…When the sparsity rate λ in (18) is unknown, it can be learned using the EM-BG procedure described in [44]. In most cases, improved performance is obtained when a Gaussian mixture (GM) pdf is used in place of the Gaussian pdf in (18) [44].…”
Section: Signal Prior Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the sparsity rate λ in (18) is unknown, it can be learned using the EM-BG procedure described in [44]. In most cases, improved performance is obtained when a Gaussian mixture (GM) pdf is used in place of the Gaussian pdf in (18) [44].…”
Section: Signal Prior Distributionmentioning
confidence: 99%
“…For example, when all coefficients x n are known to be real-valued or positive, the circular-Gaussian pdf in (18) should be replaced by a real-Gaussian or truncated-Gaussian pdf, respectively, or even a truncated-GM [45]. Furthermore, when certain coefficient subsets are known to be more or less sparse than others, a non-uniform sparsity [46] rate λ n can be used in (18).…”
Section: Signal Prior Distributionmentioning
confidence: 99%
“…2(g)]. Fortunately, it is often possible to infer the lost phase information using an iterative phaseretrieval algorithm [31][32][33][34]. In essence, our approach relies on reducing the light-scattering problem to a phase-retrieval problem.…”
Section: High-resolution Spatial Information Retrievalmentioning
confidence: 99%
“…Examples include a known finite sample support [18,19], sparsity [20], non-negativity or an intensity histogram [21]. Several recent works examine how sample sparsity permits accurate sample reconstruction from a limited number of holographic measurements [15,[22][23][24][25][26][27][28][29][30]. To the best of our knowledge, no work has yet examined whether prior knowledge of sample support alone may also relax required in-line holographic image readout rates, nor has demonstrated that such a modified phase retrieval process can improve the frame rate of on-chip holographic video.…”
Section: Introductionmentioning
confidence: 99%